Evaluation of the effect of phenolic pigments on rice germination under low temperature conditions - Maltzahn, Latóia Eduarda; Viana, Vívian Ebeling; Aranha, Bianca Camargo; Custódio, Tiago Vega; Venske, Eduardo; Maia, Luciano Carlos da; Oliveira, Antonio Costa de; Pegoraro, Camila (Revista de Ciências Agroveterinárias, 2022)
In Rio Grande do Sul, the main rice producer State in Brazil, low temperatures can occur during germination and seedling establishment, and in some cases, during the reproductive stage. When low temperatures occur in the early developmental stages cause delay in germination, resulting in a non-homogeneous growing. In reproductive stage, low temperatures cause spikelet sterility, directly interfering with plant yield. Researchers have shown that some phenolic compounds such as proanthocyanidins and anthocyanin are associated with low temperature tolerance in plants due to their antioxidant capacity. The red and black color in the seeds of some rice genotypes is conferred by the phenolic compounds proanthocyanidins and anthocyanin, respectively. Therefore, tis study aimed to verify whether rice genotypes with red or black seeds are more tolerant to low temperatures during germination. In this study, five rice genotypes were tested, two present seeds without pigmentation and with contrasting response to low temperature tolerance (BRS Bojuru - tolerant and BRS Pampeira - sensitive), two genotypes with red seeds (BRS 902, SCS 119 Rubi) and one black seed genotype (SCS 120 Ônix). As expected, the genotypes with pigmented seeds had a greater total phenolic compounds content. However, under low temperature conditions, the genotypes with pigmented seed showed a similar response to the sensitive genotype. Therefore, the presence of proanthocyanidins and anthocyanin in the seed of the studied genotypes does not provide tolerance to low temperatures during germination.